The Effect of Small Group Discussion on Students’ Achievement in Reading Narrative Text at the Third Year Students of MTs Al-Washliyah 30 Pematang Guntung - Windinoviasari Lubis; Asnawi (Education & Learning, 2022)
The objective of this study was to get the empirical evidence of the effect of using small group discussion technique on students’ achievment in reading narrative text at the third year students of MTS AL-Washliyah 30 Pematang Guntung. The method used in this study was quantitative through quasi experimental research. The population was all the third year students of MTS AL-Washliyah 30 Pematang Guntung. The total sample was 60 students that were taken by using lecturing technique Instrument of this study was multiplechoise test. Before doing the treatment, the students in experimental class were given the pre-test. Then, the students were taught by using small group discussion technique. At the end of the treatments, the students were given a post-test. T-test was used to analyze the data. Value of tobserve is 4.75 and the degree of freedom (df) is 58, whereas the value t-table on the degree of significance of 5% is 1.67. The T-test revealed that the result is significant; it is determined by the value of t Obsever which is bigger than t table. Thus, Ha is accepted because there is significant effect of using small group discussion on students’reading narrative text ability. Therefore, it can be concluded that using small group discussion is effective to improve students reading narrative text ability at the third year students of MTS AL-Washliyah 30 Pematang Guntung.